STUDI LITERATUR: ANALISIS PENGARUH FINANCIAL DISTRESS DAN REPUTASI KAP TERHADAP AUDIT DELAY - Kartika, Prilcilia; Yudiah, Mutiara Octaviani (Universitas Prof.Hazairin,SH Bengkulu, 2023)
This study purpose to describe the development of any elements that can affect audit delay, especially how the effect of financial distress and KAP’s reputation. This research is a qualitative research where researchers use the Systematic Literature Review method. Data collection in this literature study uses publish or perish or POP with the Google Scholar search engine based on publications in 2013 – 2023.The keywords is used when searching with Google Scholar such as financial distress, KAP’s reputation and audit delay. From this search, only journal articles that have been indexed by Sinta were taken and 35 journal articles were selected according to the sample selection category. The results obtained are the financial distress and KAP reputation variables that affect audit delay.